1988
DOI: 10.1002/1097-0142(19880801)62:3<564::aid-cncr2820620321>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in advanced nonseminomatous testicular cancer a multivariate logistic regression analysis

Abstract: In order to define prognostic factors for advanced stage of nonseminomatous germ cell tumors (NSGCT) of the testis, the authors reviewed 84 patients treated from 1978 through 1985. The survival rate was 51% at 3 years. Patients with elevated seric levels of human chorionic gonadotropin (HCG) and/or alpha-fetoprotein (AFP), or the presence of an abdominal mass had significantly worse survival. Only HCG and AFP levels retained their significance when multivariate Cox analysis was performed. The probability that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(24 citation statements)
references
References 12 publications
0
23
0
1
Order By: Relevance
“…For reducing these risks, some researchers proposed adept treatment strategy and the interval CT follow-ups depending on risk factors of relapse. In the last three decades, multiple predictive factors for LN metastases or relapse were explored in TC [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These predictors are mainly divided into two groups: serum tumor markers, including AFP, Beta-HCG, and lactate dehydrogenase (LDH); tumor histopathological characteristics, including size, histological percentage (embryonal carcinoma and teratoma), lymphovascular, epididymis, rete testis and tunic invasions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reducing these risks, some researchers proposed adept treatment strategy and the interval CT follow-ups depending on risk factors of relapse. In the last three decades, multiple predictive factors for LN metastases or relapse were explored in TC [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These predictors are mainly divided into two groups: serum tumor markers, including AFP, Beta-HCG, and lactate dehydrogenase (LDH); tumor histopathological characteristics, including size, histological percentage (embryonal carcinoma and teratoma), lymphovascular, epididymis, rete testis and tunic invasions.…”
Section: Discussionmentioning
confidence: 99%
“…The potential risk factors on lymph node metastasis in testicular GCTs(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) …”
mentioning
confidence: 99%
“…Trials after announcement of IGCCCG criteria in 1997 have aimed to identify predictive and prognostic factors for the 20-30% of the patients group who did not have complete remission and who died because of their disease. In the literature published before 1997 in which factors influencing complete response were searched, elevation of levels of tumor markers, especially beta HCG and AFP (Droz et al, 1988;Hanson et al, 1993;Schmoll and Beyer, 1998;Stoter et al, 1987),non-pulmonary metastasis and retroperitoneal tumor size (Javadpour and Young, 1986;Aass et al, 1991;Hanson et al, 1993) were reported as predictive factors. In a recently published retrospective study, rate of decline of tumor marker levels is also reported to have a predictive value (Keskin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…18 Choriocarcinoma, as a component of a mixed tumor in the histology of the primary tumor, does not predict an adverse outcome. 19 However, patients with advanced pure choriocarcinoma or choriocarcinoma syndrome have a worse prognosis than other advanced/poor prognosis nonseminomatous GCTs, because of the very high levels of hCG and propensity for pulmonary and nonpulmonary visceral metastases. Batata 20 reported a series of pure choriocarcinoma with no long-term survival.…”
Section: Discussionmentioning
confidence: 99%